Lattice Boltzmann Simulations of Water Transport from the Gas Diffusion Layer to the Gas Channel in PEFC (Communications in Computational Physics, 2020)
Water management is a key to ensuring high performance and durability ofpolymer electrolyte fuel cell (PEFC), and it is important to understand the behavior ofliquid water in PEFC. In this study, the two-phase lattice Boltzmann method is appliedto the simulations of water discharge from gas diffusion layers (GDL) to gas channels.The GDL is porous media composed of carbon fibers with hydrophobic treatment,and the gas channels are hydrophilic micro-scale ducts. In the simulations, arbitrarilygenerated porous materials are used as the structures of the GDL. We investigate theeffects of solid surface wettabilities on water distribution in the gas channels and theGDL. Moreover, the results of X-ray computed tomography images in the operatingPEFC are compared with the numerical simulations, and the mechanism of the watertransport in PEFC is considered.